A CyberPragmatic Study of Exaggeration on the YouTube Platform - Muthanna Hasan; Hasan Al-Kaabi (آداب الكوفة)
Exaggeration is a common technique on the Internet, where people can express their opinions and feelings in a creative and sometimes funny way.